Efficiency analysis of financial system: Evidence from Turkish banking industry using DEA bootstrap method - Saeid Hajihassaniasl (New Applied Studies in Management, Economics & Accounting)
The main purpose of this study is to compare the technical efficiency of deposit banks operating in the Turkish banking sector in year 2019 and 2020 separately. Input-oriented bootstrap DEA approach was used under the assumption of variable returns to scale with seven inputs and a single output to make the estimations in this study. A total of 25 deposit banks were included in the analysis, and estimates were made for 2019 and 2020 years separately. According to the results of the study, provided that the inputs used by the banks remain constant, while there is a potential of 9% in the credits given in 2019, this rate was approximately 11% in the first year of the Covid-19 epidemic 2020. This shows that in 2020, compared to the 2019, the mean efficiency of banks decreased by 2%. Also at this period, state banks were more efficient than private Banks. So it is necessary forming a competitive platform for improving the private banks efficiency.